2010
DOI: 10.1097/01.aids.0000386733.02425.98
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS among female sex workers, injecting drug users and men who have sex with men in Lebanon: results of the first biobehavioral surveys

Abstract: Prevention efforts at greater scale are needed to reach these at-risk populations in Lebanon. These should target MSM in particular, including access to HIV testing, but will need to address and overcome stigma. For IDUs, surveillance and prevention efforts should integrate both hepatitis C virus and HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
74
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 7 publications
8
74
3
1
Order By: Relevance
“…Likewise, enjoyment associated with group sex practices and their preference to experience sexual sensation without condoms, coupled with the unavailability of condoms at time when such practices happened, were enablers to MSM engagement in UAI. Findings of the current study conform to previous studies (Egypt Ministry of Health and Population National AIDS Program, 2006;El-Sayed, et al, 1994;Elrashied, 2006;Mahfoud, Afifi, Ramia, El-Khoury, & Kassak, 2010), including, that participants' engagement in transactional sex practices as male sex workers put them in a weak position for safe sex negotiation. These findings also support results of previous studies (Balán, et al, 2009;Berg & Grimes, 2010;Elford, Bolding, & Sherr, 2001;Mettey, Crosby, DiClemente, & Holtgrave, 2003;Poon, et al, 2013), that inform the use of internet to meet online sex partners for offline sex and transactional sex as the common practices that contributed to unprotected sexual behaviours among MSM populations.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, enjoyment associated with group sex practices and their preference to experience sexual sensation without condoms, coupled with the unavailability of condoms at time when such practices happened, were enablers to MSM engagement in UAI. Findings of the current study conform to previous studies (Egypt Ministry of Health and Population National AIDS Program, 2006;El-Sayed, et al, 1994;Elrashied, 2006;Mahfoud, Afifi, Ramia, El-Khoury, & Kassak, 2010), including, that participants' engagement in transactional sex practices as male sex workers put them in a weak position for safe sex negotiation. These findings also support results of previous studies (Balán, et al, 2009;Berg & Grimes, 2010;Elford, Bolding, & Sherr, 2001;Mettey, Crosby, DiClemente, & Holtgrave, 2003;Poon, et al, 2013), that inform the use of internet to meet online sex partners for offline sex and transactional sex as the common practices that contributed to unprotected sexual behaviours among MSM populations.…”
Section: Discussionsupporting
confidence: 89%
“…Most of them had attended school and could read and write but some had completed university education. These findings are in accordance with findings of most studies on FSW in the Middle East and North Africa [12][13][14][15]. On the other hand, most of the FSW had been married at a relatively young age.…”
Section: Discussionsupporting
confidence: 91%
“…The same finding was obtained in our study where more than one-third of the studied sex workers reported having sex under the threat of abuse or abusive sex, which was mostly physical. Violence is associated with unprotected sex and increases the risk of HIV infection due to vaginal trauma and lacerations resulting from the use of force [2,[15][16][17][18]. Sexually transmitted infections (STIs) are common among FSWs as shown by different studies [19][20][21].…”
Section: Discussionmentioning
confidence: 99%